Program Peningkatan Kemampuan Komunikasi Dengan Storytelling Bersumber pada Ithihasa Hindu di IAHN Gde Pudja Mataram - Dewi, Ni Luh Sinar Ayu Ratna; Yadnya, Suci Raditya; Patni R, Gusti Ayu Santi; Saridewi, Desak Putu; Zaenab, Siti; Yadnya, Made Sutha (Jurnal Gema Ngabdi, 2025)
The ability to communicate with stories is a special thing for generation Z. Telling stories with the works composed by Rsi and Bagawan in their time which until now continues to be used in the delivery of religious values, both positive norms and sebalikaya norms. The problem is that in the delivery of the story, it is necessary to appreciate and mimic expression.  The favorite story in Ithihasa is a Hindu story with a heroic study with a thick narration (Ramayana and Mahabrata). The spirit of heroism in the story evokes nationalism for love for the homeland and nation in the corridors of the Republic of Indonesia. One of the steps taken for the implementation of this program is a storytelling competition. The target of the competition is so that stories can go international by telling stories in English as an International Language. The competition began and was attended by representatives of schools and students in Mataram City. The enthusiasm for participating in the storytelling competition   was very enthusiastic.